Allogeneic hematopoietic cell transplantation in intermediate risk acute myeloid leukemia negative for FLT3-ITD, NPM1- or biallelic CEBPA mutations - Heidrich, Katharina; Krämer, Alwin (Annals of oncology, 2017)
Background: The value of allogeneic hematopoietic cell transplantation (alloHCT) as postremission treatment is not well defined for patients with intermediate-risk acute myeloid leukemia (AML) without FLT3-ITD, biallelic CEBPA-, or NPM1 mutations (here referred to as NPM1mut-neg/CEBPAdm-neg/FLT3-ITDneg AML) in first complete remission (CR1). Patients and methods: We addressed this question using data from two prospective randomized controlled trials on intensive induction- and risk-stratified postremission therapy. The NPM1mut-neg/CEBPAdm-neg/FLT3-ITDneg AML subgroup comprised 497 patients, aged 18-60 years. Results: In donor versus no-donor analyses, patients with a matched related donor had a longer relapse-free survival (HR 0.5; 95% CI 0.3-0.9, P = 0.02) and a trend toward better overall survival (HR 0.6, 95% CI 0.3-1.1, P = 0.08) compared with patients who received postremission chemotherapy. Notably, only 58% of patients in the donor group were transplanted in CR1. We therefore complemented the donor versus no-donor analysis with multivariable Cox regression analyses, where alloHCT was tested as a time-dependent covariate: overall survival (HR 0.58, 95% CI 0.37-0.9, P = 0.02) and relapse-free survival (HR 0.51, 95% CI 0.34-0.76; P = 0.001) for patients who received alloHCT compared with chemotherapy in CR1 were significantly longer. Conclusion: Outside clinical trials, alloHCT should be the preferred postremission treatment of patients with intermediate risk NPM1mut-neg/CEBPAdm-neg/FLT3-ITDneg AML in CR1.Cinicaltrials.gov identifierNCT00180115, NCT00180102
Gesehen am 12.04.2018